Vibrational intensities - Galabov, Boris S. (Vibrational spectra and structure, 1996)
The current volume is a single topic volume on the vibrational intensities in the infrared and Raman spectra. Vibrational intensities in infrared and Raman spectra are important physical quantities that are directly related to the distribution and fluctuations of electric charges in the molecule. These spectral parameters can be experimentally determined with good accuracy for many molecules. Additionally, infrared and Raman intensities are presently estimated theoretically by advanced analytical derivative ab initio molecular orbital methods. These fundamental molecular quantities are being used in structural, and other studies, on a limited basis. Features of this book - Presents in a systematic way, the theoretical approaches that are used in analyzing and predicting vibrational intensities - The formalisms developed are illustrated with detailed numerical examples - Most of the theoretical models described were obtained and then applied to chosen molecules - A consistent notation is used in presenting the different theoretical approaches, thus eliminating another barrier in understanding some methods, especially those developed by the Russian spectroscopic school.